Polystyrene nanoparticles affect the innate immune system of the Antarctic sea urchin Sterechinus neumayeri - Bergami, E.; Krupinski Emerenciano, A.; González-Aravena, M.; Cárdenas, C. A.; Hernández, P.; Silva, J. R. M. C.; Corsi, I. (Polar biology, 2019)
Plastic debris has been recognised as a potential stressor for Antarctic marine organisms. In this study, the effects of surface charged polystyrene nanoparticles (PS NPs) on the immune cells (coelomocytes) of the Antarctic sea urchin Sterechinus neumayeri were assessed through in vitro short-term cultures. The behaviour of anionic carboxylated (PS-COOH) and cationic amino-modified (PS-NH 2 ) NPs in filtered natural sea water (NSW) from King George Island (South Shetland Islands) was characterised by dynamic light scattering. Cellular morphology, NP uptake, phagocytic capacity and gene expression were evaluated after 6 and 24 h of exposure to 1 and 5 µg mL −1 PS NPs. Secondary characterisation showed an initial good dispersion of PS NPs in NSW, followed by nano-scale aggregation after 24 h. Both PS NPs affected cellular phagocytosis and generated an inflammatory response against oxidative stress and apoptosis at the molecular level. Fluorescently labelled PS-COOH aggregates were internalised by phagocytes and associated to the modulation of genes related to external challenges, antioxidant responses and cell protection against stress and apoptosis. Exposure to PS-NH 2 caused a strong decrease in phagocytic capacity and the formation of cellular debris at 5 µg mL −1 after 24 h, but low gene modulation, suggesting a threshold in coelomocytes defence ability against PS-NH 2 . This study represents the first attempt to assess the impact of nanoplastics on Antarctic marine organisms. Our findings demonstrate that PS NPs with different surface charges constitute a challenge for S. neumayeri immune cells.